Use of Visit Karakalpakstan Mobile App in the Development of Tourism in the Republic of Karakalpakstan - Madaminov Uktamjon Ataxanovich; Qodirov Davronbek Rajabboy o‘g‘li; Avezov Mardonbek Abdullayevich; To‘liboyeva Umida Gulmirza qizi (Research Parks Publishers, 2021)
This article provides detailed information about a mobile app that will serve the further development of the tourism industry in the Republic of Karakalpakstan.